Violations of the Principles of Democracy and People's Sovereignty Related to Bureaucracy in Central Sulawesi - Nazwa Defa; Vera Desti Puspitasari; Alicya Rahmawati; Ahmad Rifki Hanafi (JILPR Journal Indonesia Law and Policy Review, 2023)
This study means to link violations committed by bureaucratic officials in the Indonesian region with the principles of Indonesian constitutional law, namely the principles of democracy and the principle of people's sovereignty, which are in accordance with the legal basis, by the Amendment to Article 1 paragraph (2) of the 1945 Constitution by the MPR. Regarding Indonesian sovereignty which is in the hands of the people and carried out in accordance with the Constitution. This study uses the Normative Juridical method, which means that research is carried out by examining legal regulations and other supporting materials that are still related to violations committed by government bureaucrats against the principles of constitutional law, namely the principles of democracy and people's sovereignty. This research is based on descriptive characteristics, namely research that has the plan to describe events related to the topic of this research. From this study, it is clear that the appointment of regional head officials without elections by the people is against the principle of popular sovereignty and the principle of democracy. In this case, the participation and responsibility of all Indonesian citizens are needed to create a democratic system that is fair, equitable, and beneficial for the entire Indonesian government.